Apostolic Evangelism in the Postcolony - Yong, Amos (Mission studies, 2017)
What does evangelism, the proclamation of the Christian gospel, look or sound like in a postcolonial era, a time in which there is a reluctance to assert a metanarrative that marginalizes the many voices of the pluralistic public sphere? Surprisingly, perhaps like how it may have originally gone forth in the first century via the apostolic followers of Jesus the Messiah. This essay suggests a re-reading of Luke-Acts, via what might be called a Pentecostal hermeneutic, one informed by foregrounding the Day of Pentecost narrative of the Spirit poured out on all flesh, in order to sketch an apostolic theology of evangelistic praxis for the contemporary post-colony.